NGHIÊN CỨU ĐỘNG HỌC SỰ TẠO THÀNH PHỨC TRUNG GIAN HOẠT ĐỘNG PEROXO TRONG HỆ: H2O–Co2+–Axetylaxeton (Acac)–H2O2 (1) - Huỳnh, Lê Văn; Xuyến, Nguyễn Văn; Tuyền, Nguyễn Minh (Vietnam Journal of Chemistry, 2012)
In this paper we present the results of kinetic studies the formation and decomposition of intermediate complex activities Peroxo (Per) in the system: H2O – Co2+ – Acac –H2O2 (1), determine the maximum absorption wavelength of the complex Per, factors affecting the rate of H2O2 decomposition reaction, while setting the dynamical equations of per complex.